The impact of disruptions due to COVID‐19 on HIV transmission and control among men who have sex with men in China. Issue 4 (6th April 2021) - Booton, Ross D; Fu, Gengfeng; MacGregor, Louis; Li, Jianjun; Ong, Jason J; Tucker, Joseph D; Turner, Katherine ME; Tang, Weiming; Vickerman, Peter; Mitchell, Kate M
Abstract: Introduction: The COVID‐19 pandemic is impacting HIV care globally, with gaps in HIV treatment expected to increase HIV transmission and HIV‐related mortality. We estimated how COVID‐19‐related disruptions could impact HIV transmission and mortality among men who have sex with men (MSM) in four cities in China, over a one‐ and five‐year time horizon. Methods: Regional data from China indicated that the number of MSM undergoing facility‐based HIV testing reduced by 59% during the COVID‐19 pandemic, alongside reductions in ART initiation (34%), numbers of all sexual partners (62%) and consistency of condom use (25%), but initial data indicated no change in viral suppression. A mathematical model of HIV transmission/treatment among MSM was used to estimate the impact of disruptions on HIV infections/HIV‐related deaths. Disruption scenarios were assessed for their individual and combined impact over one and five years for 3/4/6‐month disruption periods, starting from 1 January 2020. Results: Our model predicted new HIV infections and HIV‐related deaths would be increased most by disruptions to viral suppression, with 25% reductions (25% virally suppressed MSM stop taking ART) for a three‐month period increasing HIV infections by 5% to 14% over one year and deaths by 7% to 12%. Observed reductions in condom use increased HIV infections by 5% to 14% but had minimal impact (<1%) on deaths. Smaller impacts on infections and deaths (<3%) were seen for disruptions to facility HIV testing and ART initiation, but reduced partner numbers resulted in 11% to 23% fewer infections and 0.4% to 1.0% fewer deaths. Longer disruption periods (4/6 months) amplified the impact of disruption scenarios. When realistic disruptions were modelled simultaneously, an overall decrease in new HIV infections occurred over one year (3% to 17%), but not for five years (1% increase to 4% decrease), whereas deaths mostly increased over one year (1% to 2%) and five years (1.2 increase to 0.3 decrease). Conclusions: The overall impact of COVID‐19 on new HIV infections and HIV‐related deaths is dependent on the nature, scale and length of the various disruptions. Resources should be directed to ensuring levels of viral suppression and condom use are maintained to mitigate any adverse effects of COVID‐19‐related disruption on HIV transmission and control among MSM in China.